Az Európai Számvevőszék ellenőrzési tevékenységének kohéziós politikai vetülete - Nagy, Sándor (Közép-Európai Közlemények, 2012)
As a result of the unfavourable global processes, the EU’s ability to sustain a sufficient standard of living according to the share of the global GDP, is in real, perceptible danger. In order to avoid the gloomy scenario, and to handle the unpredictable risks the European Commission is getting framing new strategies. These long term conceptions contain priorities, which serve as guideline to reach the goals, objects proposed. To enhance the competitiveness of the EU there are several (direct and indirect) means to apply. One of these is the less known European Court of Auditors (ECA). The ECA –in the course of its functions –contributes to the financially effective, economical, efficient, regular and transparent priority oriented use of the sources of the EU-budget, and hereby catalyzing the development of the competitive features. Henceforth I represent the functional activity, work of the European Court of Auditors regarding the cohesion policy and the linkage to the general competitivness.